2013
DOI: 10.21236/ada595841
|View full text |Cite
|
Sign up to set email alerts
|

Shock Tunnel Operation and Correlation of Boundary Layer Transition on a Cone in Hypervelocity Flow

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Experiments in this study were conducted in the T5 reflected-shock tunnel at Caltech. The facility design and operation are detailed in Hornung (1992) and Jewell (2014) and described here briefly. A schematic of T5 is shown in figure 1.…”
Section: Facility and Set-upmentioning
confidence: 99%
“…Experiments in this study were conducted in the T5 reflected-shock tunnel at Caltech. The facility design and operation are detailed in Hornung (1992) and Jewell (2014) and described here briefly. A schematic of T5 is shown in figure 1.…”
Section: Facility and Set-upmentioning
confidence: 99%
“…A higher coefficient of determination indicates higher repeatability. Jewell et al [26,46] showed that the tunnel parameters h res (reservoir enthalpy) and P res (reservoir pressure) could be used as predictor variables to construct statistically significant linear models of transition Reynolds number Re Tr for both the present data sets and the historical T5 transition data of Germain and Hornung [17] and Adam and Hor-nung [18] for air, CO 2 , and N 2 . In the present work, only air transition data is considered.…”
Section: Transition Onset Correlationsmentioning
confidence: 99%
“…[4][5][6] In these facilities, researchers commonly utilize the connection of turbulence with aerodynamic friction and hence heat transfer 7 to determine the transition location. 8 Techniques such as infrared thermography, 9,10 thermocouples, 8,11 thin film gauges, 12,13 atomic layer thermopiles (ALTP), 14,15 and temperature sensitive paint 16 are used in the field to infer instability data or laminar-turbulent transition from surface heat flux recordings. However, when a cooling technique is present, surface instruments are evidently subject to coolant and boundary layer gas simultaneously and may therefore be unable to accurately resolve turbulent heating.…”
Section: Introductionmentioning
confidence: 99%
“…If gas is transpired out of the wall, it will impact transition. 11,24,25 Moreover, the state of the boundary layer also influences the cooling quality. 27 Transpiration cooling runs at risk of advancing transition 25 which was discovered in the 1950s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation